Analisis Psikologis pada Naskah Monolog HARI TERAKHIR SEORANG TERPIDANA MATI Karya Victor Hugo - Muhammad Hanif Hukama; Apsi Nugraha; Risma Ayu Destrian (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Psychology in the Monologue Script "The Last Day of a Death Row Convict" by Victor Hugo discusses the psychology of the main character in the text. This script shows the main character who is on death row and experiencing significant psychological changes. This analysis uses a psychoanalytic approach to understand how the main character faces the death penalty and how these psychological changes influence his behavior. The results of the analysis show that the main character experiences complex and dynamic psychological changes. He experienced depression, hopelessness, and anxiety related to the death sentence he faced. The conclusion of this analysis is that Victor Hugo's "The Last Day of a Death Row Convict" presents a complex and dynamic main psychological character. Psychoanalysis helps understand how the main character faces the death penalty and how these psychological changes influence his behavior. The results of this analysis can be used to understand the psychology of individuals who face difficult situations and how they develop strategies to deal with these situations.